It’s Not Easy Building Green: The Impact of Public Policy, Private Actors, and Regional Logics on Voluntary Standards Adoption - York, Jeffrey G.; Vedula, Siddharth; Lenox, Michael J. (Academy of Management Journal, 2018)
Human-induced climate change is one of the most daunting challenges of the 21st century. Addressing climate change will require new sectors that create economically and ecologically sustainable products and services, often supported through voluntary certification standards. For example, the Leadership in Energy and Environmental Design (LEED) voluntary certification standard seeks to reduce the environmental impacts of buildings through stimulating growth of the “green building” sector. Both public and private actors have attempted to promote such standards; however, we know little about the relative efficacy of such efforts. We know even less about how regional culture conditions the impact of such public and private promotion. In this study, we theorize and test how regional institutional logics filter the efficacy of public and private efforts to promote adoption of standards. Our results demonstrate that, in addition to policy, private actors such as social movement organizations, market intermediaries, and environmental entrepreneurs play a role in bolstering adoption. Yet, the efficacy of such interventions is dependent upon variations in regional culture; only environmental entrepreneurs were able to bridge the cultural divide and be equally effective in regions dominated by either market or community logics. Our findings advance understanding of how new markets are socially constructed and the conditions under which efforts to promote new sectors are more effective.